2018
DOI: 10.3390/ijms19123889
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of the Grapevine JAZ7 Gene in Arabidopsis Confers Enhanced Resistance to Powdery Mildew but Not to Botrytis cinerea

Abstract: Jasmonate ZIM-domain (JAZ) family proteins comprise a class of transcriptional repressors that silence jasmonate-inducible genes. Although a considerable amount of research has been carried out on this gene family, there is still very little information available on the role of specific JAZ gene members in multiple pathogen resistance, especially in non-model species. In this study, we investigated the potential resistance function of the VqJAZ7 gene from a disease-resistant wild grapevine, Vitis quinquangular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 105 publications
(120 reference statements)
1
5
0
Order By: Relevance
“…In this current study, JArelated genes (JAZ, LOX, AOC and AOS) were up-regulated at early time points in the HR grape and at late time points in the HS grape. We previously reported that JAZ7is a candidate gene for conferring for resistance to powdery mildew infection in grape [51], which is consistent with studies showing that many herbivory-and pathogen-induced responses in grapevines are mediated by the JA pathway [28,52]. In contrast, SA signaling is typically involved in plant resistance to biotrophic pathogens [53], with the positive SA regulator EDS1 conferring basal defense against various pathogens by interacting with a subset of plant resistance (R) genes [54].…”
Section: Discussionsupporting
confidence: 80%
“…In this current study, JArelated genes (JAZ, LOX, AOC and AOS) were up-regulated at early time points in the HR grape and at late time points in the HS grape. We previously reported that JAZ7is a candidate gene for conferring for resistance to powdery mildew infection in grape [51], which is consistent with studies showing that many herbivory-and pathogen-induced responses in grapevines are mediated by the JA pathway [28,52]. In contrast, SA signaling is typically involved in plant resistance to biotrophic pathogens [53], with the positive SA regulator EDS1 conferring basal defense against various pathogens by interacting with a subset of plant resistance (R) genes [54].…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, MpJAZ, a homolog of AtJAZ, regulated cell growth and reproductive fitness in Marchantia polymorpha [43]. In addition, overexpression of VqJAZ7 enhanced resistance to powdery mildew by controlling cell death and the accumulation of superoxide anions [44]. TaJAZ1 positively regulated powdery mildew resistance via up-regulating expression of defense-related gene TaPR1/2 and increasing reactive oxygen species accumulation in wheat [45].…”
Section: Introductionmentioning
confidence: 99%
“…According to the different life styles, plant pathogens can be divided into biotrophs (which prefer living cells) and necrotrophs (which prefer dead cells) (Barna et al, 2012). In the case of necrotrophic pathogens such as Botrytis cinerea , cell death and tissue necrosis caused by accumulation of reactive oxygen species during pathogen infection were reported to benefit pathogen invasion by offering a growth substrate, thus increasing host susceptibility (Hanif et al, 2018; Tian et al, 2019; Wang et al, 2018). F. verticillioides is a necrotrophic fungal pathogen (Rivas‐San Vicente et al, 2013).…”
Section: Discussionmentioning
confidence: 99%